2013
DOI: 10.1007/s13197-013-0938-6
|View full text |Cite
|
Sign up to set email alerts
|

Functional analysis of unfermented and fermented citrus peels and physical properties of citrus peel-added doughs for bread making

Abstract: Several studies have indicated citrus peels (CP) contain specific methoxy flavones, e.g. nobiletin and tangeretin, which have been shown to prevent numerous diseases. However, research reports regarding their application as food additive in healthy baked products is scarce. In our study, both unfermented (UF) and fermented (F) citrus peels were processed under different dry hot-air temperatures to make four citrus peel powders , UF-100°C,UF-150°C, F-100°C, F-150°C, respectively. The analysis of the basic compo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 18 publications
0
17
0
1
Order By: Relevance
“…The increase of the viscoelastic moduli, G' and G'' (Ktenioudaki et al, 2013;Pathak et al, 2016) and resistance to extension, i.e. decreased extensibility (Ktenioudaki et al, 2013;Bchir et al, 2014;Fu et al, 2015;Wu and Shiau, 2015), of doughs containing FVB confirm the need for adding more water to the formulation and, in some cases, the need for extending the kneading time (Bchir et al, 2014;Shyu et al, 2014;Chareonthaikij et al, 2016). The same authors also observed that doughs containing FVB possessed lower kneading stability, except for Bchir et al (2014), who found unusually low optimum kneading parameters.…”
Section: Physical and Sensory Quality Of Bread As Affected By Fvbmentioning
confidence: 88%
See 2 more Smart Citations
“…The increase of the viscoelastic moduli, G' and G'' (Ktenioudaki et al, 2013;Pathak et al, 2016) and resistance to extension, i.e. decreased extensibility (Ktenioudaki et al, 2013;Bchir et al, 2014;Fu et al, 2015;Wu and Shiau, 2015), of doughs containing FVB confirm the need for adding more water to the formulation and, in some cases, the need for extending the kneading time (Bchir et al, 2014;Shyu et al, 2014;Chareonthaikij et al, 2016). The same authors also observed that doughs containing FVB possessed lower kneading stability, except for Bchir et al (2014), who found unusually low optimum kneading parameters.…”
Section: Physical and Sensory Quality Of Bread As Affected By Fvbmentioning
confidence: 88%
“…A limited number of studies have focused on the effect of previous processing of FVB, such as drying or milling, on the quality of breads. Shyu et al (2014) observed that low drying temperatures (100 instead 150 o C) improved the acceptability of breads made with citrus peel, although high temperature increased the presence of phenolics and antioxidant properties of citrus peel. The authors mentioned that the higher content of highly astringent polyphenols could have reduced the acceptability of such breads.…”
Section: Effects Of the Physical Properties And Composition Of Fvb Onmentioning
confidence: 96%
See 1 more Smart Citation
“…The search for innovative technologies geared towards valorising plant-based food by-products for food product development is currently of research interest. Consequently, the application of pre-treatment processes to these plant-based food by-products, including fermentation [13][14][15], freeze-drying [16], oven-drying [17], and other thermal treatments, have been explored to enhance the bioactive and aromatic profiles of plant-based food by-products, improve their techno-functional properties, and increase their potential to be used in composite formulations with wheat flour for bread reformulation.…”
Section: Introductionmentioning
confidence: 99%
“…На промышленную переработку в продукцию направляется в среднем 30% вторичного сырья. На консервных заводах отходы, образующиеся при переработке фруктов и овощей, некондиционное сырье, а также вторичное сырье перерабатывают на следующую продукцию: фруктовые и овощные порошки, пектин, сухие выжимки, пюре, красители, ароматические вещества, крахмал, этиловый спирт, углеводы, биохимический уксус, заливочные жидкости, лечебно-профилактические препараты и прочее [4,5,[8][9][10].…”
Section: Introductionunclassified